Nonlinearly coded signals for harmonic imaging - NOWICKI, Andrzej; WÓJCIK, Janusz; KUJAWSKA, Tamara (Archives of Acoustics, 2009)
In this paper a new method utilizing nonlinear properties of tissues to improve contrast-to-noise ratio is presented. In our novel method the focused circular transducer is excited with two-tone bursts (including the 2.2MHz fundamental and 4.4MHz second harmonic frequencies) with specially coded polarization of each tone. This new approach was named Multitone Nonlinear Coding (MNC) because the choice of both tones polarization and amplitude law, allowing optimization of the probe receiving properties, depends on nonlinear properties of tissue. The numerical simulations of nonlinear fields in water and in tissue-like medium with absorption coefficient of 7Np/(m MHz) are performed. The comparison between the proposed method and the Pulse Inverse (PI) method is presented. The concept of the virtual fields was introduced to explain properties of both the Pulse Inversion and MNC methods and to compare their abilities. It was shown that for the same on-source pressure an application of the MNC method allows to decrease the mechanical index about 40%, to improve lateral resolution from 10 to 30% and to gain the signal-to-noise ratio up to 8 times with respect to the PI method.